Covalent Bridges in Bi Loaded BiVO4 Enabling Rapid Charge Transfer for Efficient Photocatalytic Water Oxidation - Liyang Li; Zhiming Chen; Dong Fang; Jingxiang Low; Jianhong Yi (Advanced Science)
Abstract Bismuth vanadate (BiVO4) is known as one of the most potential candidates in photocatalytic water oxidation for supplying oxygen in extreme environment. However, its photocatalytic oxygen evolution is hindered by the rapid photogenerated charge carrier separation efficiency. Herein, plasmonic bismuth (Bi) nanoparticles loaded BiVO4 is prepared for photocatalytic water oxidation. Specifically, the plasmonic bismuth nanoparticles are in situ loaded on the BiVO4 via reduction of partial BiVO4, allowing the formation of the Bi─O─V covalent bridges. Based on the femtosecond transient absorption spectroscopy and density functional theory calculations, such Bi─O─V covalent bridges can significantly facilitate the migration of the plasmonic‐induced hot electrons from Bi to BiVO4, allowing more photogenerated charge carrier to participate in the surface reaction. As a result, the optimized Bi/BiVO4 demonstrates a record‐high photocatalytic evolution rate of 4567.94 µmol h−1 g−1. More importantly, the obtained Bi/BiVO4 show plausible photocatalytic water oxidation capability (oxygen production rate of 381.47 µmol h−1 g−1) under near‐infrared light irradiation, further collaborating its potential to be utilized in extreme conditions. This work on design of low‐cost and highly‐efficient photocatalysts for water oxidation is anticipated to push forward the development of photocatalytic oxygen production in various application scenarios.